Shale gas characterization of the Dinder and Blue Nile Formations in the Blue Nile Basin, East Sudan - Shoieb, M.A. (American Institute of Physics Inc., 2016)
The development of gas and oil in unconventional plays in United State and Northern Europe has affected the finances and the energy security. Geochanical properties of shale rocks can have a major impact on the efficiency of shale gas exploration. The goal of this study is to evaluate shale gas potentiality in the Blue Nile Basin, using samples from existing drilled wells. All the samples were analyzed in detail with the following organic geochemical techniques: total organic carbon (TOC), Rock-eval pyrolysis, to determine the quality and quantity of the organic matter. The total organic carbon (TOC) values for the shale intervals vary from 0.6 to 4.5weight in FARASHA-1 Well, while in TAWAKUL-1 Well range from 0.4 to 2.4weight, suggesting that fair to good source generative potential, as revealed by the S2 v's TOC plot. Hydrogen index (HI) values range from 12 to 182 mg HC/g TOC in the two wells, indicating type III and IV derived-input in the samples and their potential to generate gas. However, the Blue Nile and Dinder Formation have Tmax values in the range of 437 to 456Â°C, indicating early maturity in the oil window. Thus, higher maturity levels have affected the hydrocarbon generation potential and HI of the samples. Â© 2016 Author(s).